Development of new hybrid jute/carbon/fishbone reinforced polymer composite. (2021) - Singh, Harsimran; Batra, N.K; Dikshit, Iti
Abstract: This article provides the details regarding the fabrication and mechanical properties of hybrid jute/carbon with the addition of fishbone as nanofiller material which has been explored the first time. The mechanical properties were compared with carbon/jute hybrid polymer composite with and without filler material i.e., fishbone. The hybrid reinforced composites with fishbone powder shows improved mechanical properties in comparison to composites fabricated without filler. Tensile strength varies from 34.91 MPa to 140.82 MPa, flexural strength varies from 66.43 MPa to 166.09 MPa, and Rockwell Hardness of the composites varies from 2.9 HRC to 35 HRC, as a function of fiber volume fraction. The tensile test, flexural test, and rockwell hardness are carried out using ASTM standards. Adding the filler in hybrid reinforced composites shows improvement in tensile strength by a maximum of 7.06%. The morphological property of flexural test specimens analyzed by scanning electron microscopy (SEM). It can be concluded, that the addition of bio nanofiller, in unsaturated polyester resin is an auspicious initiative to produce high strength unsaturated carbon /jute hybrid reinforced composite.